Nabais Sa‐de Vries syndrome in a Chinese infant associated with a novel SPOP mutation: A clinical study and genetic report. Issue 12 (19th October 2022) - Hu, Wenjing; Fang, Hongjun; Peng, Yu; Li, Li; Liu, Shulei; Liao, Hongmei; Tang, Jingwen; Yi, Jurong; Liu, Qingqing; Xu, Li; Wu, Liwen
Abstract: Background: Nabais Sa‐de Vries syndrome (NSDVS) is a newly identified neurodevelopmental disorder (NDD), characterized by mutations in the SPOP gene, which encodes the speckle‐type BTB/POZ protein. It is divided into two disease subtypes, according to patient facial features, which could be related to altered SPOP protein function. Few studies have documented this syndrome and little is known about its pathophysiology. Herein, we present an unexplained infant case of NDD, possibly the first Asian NSDVS case report. Methods: A 7‐month‐old boy presented with an enlarged head circumference, widened eye distance, and a protruding nose. Trio‐whole exome sequencing of the patient's family was performed, and a variant was identified by bioinformatics analysis and further verified by Sanger sequencing. This variant was then identified by molecular dynamics analysis. Finally, a plasmid was constructed in vitro to transfect the human 293 T cells. qPCR and western blotting (WB) experiments were subsequently performed. These analyses verified the variant's transcription and protein expression. Results: Trio‐whole exome sequencing was used to identify the SPOP mutation c.67 T > C (p.Cys23Arg). Crystal structure simulations suggest that this single‐residue substitution alters hydrogen bonding with nearby residues. Analysis via qPCR and WB experiments indicated decreased mutant mRNA and protein expression levels. Conclusion: Our findings suggest that genetic testing should be performed as soon as possible for children with NDD showing low phenotypic specificity. Prompt testing will provide more accurate diagnoses, which in turn offers evidence to assist in the formulation of rehabilitation training plans, and genetic counseling for patients' families. Abstract : Nabais Sa‐de Vries syndrome (NSDVS) is a newly identified neurodevelopmental disorder (NDD). To date, only one study has been published, so little is known. Mutations in the SPOP gene, encoding the speckle‐type BTB/POZ protein, have been shown to cause NSDVS, but patients present with varied phenotypes. We present an unexplained infant case of NDD, possibly the first Asian NSDVS case report.